Substance Use among Adolescents Involved in Bullying: A Cross-Sectional Multilevel Study - Gaete, Jorge; Tornero, Bernardita; Valenzuela, Daniela; Rojas-Barahona, Cristian A.; Salmivalli, Christina; Valenzuela, Eduardo; Araya, Ricardo (Frontiers in Psychology, 2017)
Being involved in bullying as a victim or perpetrator could have deleterious health consequences. Even though there is some evidence that bullies and victims of bullying have a higher risk for drug use, less is known about bystanders. The aim of this research was to study the association between bullying experience (as victims, bullies, or bystanders) and substance use. We gathered complete information from a nationally representative sample of 36,687 students (51.4% female) attending 756 schools in Chile. We used a self-reported questionnaire which was developed based on similar instruments used elsewhere. We pilot this questionnaire and presented to an expert panel for approval. We used multilevel multivariate logistic regression analyses, controlling for several variables at the individual (e.g. school membership, parental monitoring) and school levels (e.g. school type, school denomination). This study shows that bullies and bully-victims have a high risk for cigarette, alcohol, and cannabis use than bystanders. This is one of the few studies exploring the association between witnessing bullying and substance use. These findings add new insights to the study of the co-occurrence of bullying and substance use. Other factors, such as higher academic performance, stronger school membership, and better parental monitoring reduced the risk of any substance use, while the experience of domestic violence and the perception of social disorganization in the neighborhood, increased the risk. These findings may help the design of preventive interventions.